Grupy interesu w okresie transformacji w Polsce - Wrzeszcz-Kamińska, Grażyna (Interest groups in the transformation time in Poland, 2006)
The point of this article is subject matter creating, action and the structure of interest groups in the period of transformation. The paper discusses the theoretical conception of interest groups among other things by D. Truman, M. Olson, G. Stigler, G.A. Becker, as well as it identifies chosen operation interest groups in connection with privatisation state-owned companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1131, s. 63-74